Study of performance of nickle quarry dust composite coated cutting tool - Ibrahim, Abdullahi Abdulrazak (2020)
Cutting tools are a major important when it comes to machining. Industries and labs depend on it for their various productions. One of the most commonly used cutting tools is tungsten carbide cutting tool. This tool s reasonably priced and available in everywhere. However, one big problem industries always face is tools wearing out after couple of runs. In this project, the aim is to try and tackle the problem by experimenting a new type of cutting tool. Tungsten carbide cutting tool has the problem of wearing out quite early, so by coating it with a nickel quarry dust composite, the tool can last longer. In this project experiments will be done using this nickel quarry dust composite coated cutting tool. By using an end mill process, the performance of the cutting tool will be examined. Aluminium block will be used as a work piece. Same parameters and feed rates will be used to test the and compare the cutting tool performances. Depth of cut will be kept at constant as well. Microsoft excel will be used o analyse and compare the data to find required results.